Risk Reduction in Electrical Networks and Safety of Biomedical Equipment in Clinical Settings - Arregui, M.; Alfaro, N.; Baldizzoni, M.; Wald, I.; Gambogi, R.; Ferreira, A.; Simini, F. (Revista Mexicana de Ingenieria Biomedica, 2018)
112 field inspections to 78 high technology medical centers (IMAE is the Spanish acronym) over 14 years are analyzed. All visits were evaluated as to Clinical Engineering good practices and were assigned a risk level. All au-dits included a questionaire to maintenance management personnel on electrical network operation as well as on biomedical equipment follow-up and documentation from acquisition to disposal. Risk is assigned a level 0 to 4 at each visit. In 2004-2007, 74% of IMAEs had safety problems in one or more of electrical network, maintenance management or documentation, and 15% of the IMAEs with safety problems had one piece of equipment described as simply “dangerous”. Electrical safety problems were eventually reduced to 0% in 2016-2017, probably as a con-sequence of regular audit and counseling by this University Clinical Engineering Program.